Export-Import Customs Service Through Indonesia National Single Window - Evada Rustina; Racitra Wulan Fitrianty; Rafdy Kaukabun Nufus; Mochammad Sidiq Fathonni; Sri Sayekti Lestari (International Journal of Economics, Business and Innovation Research, 2023)
This study aims to find out what exporters and importers must do to obtain customs services, and know the process of export and import services through the Indonesia National Single Window at the Palembang Customs Type B Supervision and Customs Service Office. The method used is descriptive qualitative, using primary and secondary data. As well as data collection techniques used employing interviews and observations in the field as well as documentation and literature studies. Based on the results of research that has been carried out, it was obtained that to obtain customs access rights, exporters and importers activate the Online Single Submission (OSS) account to get a User ID and password used to obtain a Business Identification Number (NIB) which is then used to create an Indonesia National Single Window (INSW) 2 account. Export-Import Customs Service through the Indonesia National Single Window where the exporter makes PEB and the importer makes PIB which is sent to Ceisa Export and Ceisa Import which is then checked in Indonesia National Single Window, after that enter the stripping until getting an Export Service Memorandum, while the import stripping there are red, yellow, green and MITA lines until getting a Letter of Approval for Goods Expenditure